Arguing with Images as Extended Cognition - Santibáñez, Cristián (Informal Logic)

(untitled) (Informal Logic, 2018)
In this paper the role of images in argumentative settings is analyzed from a cognitive angle. In particular, the proposal of this paper is to see visual argumentation as a specific form of extended and distributed cognition. In order to develop this idea, some of Wittgenstein’s insights are used to put evidence produced by research on temporal-spatial reasoning processes into philosophical perspective. Some contemporary argumentative analyses of visual argumentation are also discussed using commercial and political examples. The paper finishes with the notion of collective minds in order to specify the general idea of arguing with images as extended cognition.